Review of exercise-induced muscle injury: Relevance for athletic populations - Falvo, M. J.; Bloomer, R. J. (Research in Sports Medicine, 2006)
Exercise-induced skeletal muscle injury is well understood as the product of unfamiliar or strenuous physical activity. Eccentric or lengthening actions are primarily responsible for inducing injury, which subsequently leads to a variety of signs and symptoms. Although significant research supports this finding, most observations are specific to untrained individuals. In addition, many protocols designed both to induce muscle injury and assess performance following the injury are dissimilar from those utilized by physically trained individuals or are impractical in relation to athletic performance or both. Therefore, difficulty may arise when extrapolating information, from the available literature and applying the findings to athletic populations. This review addresses the efficacy of applying our current understanding of exercise-induced skeletal muscle injury to a physically trained population as well as highlights concerns that require future investigation.